Association between admission inflammatory indicators and 3-year mortality risk in geriatric patients after hip fracture surgery: a retrospective analysis of a prospective cohort study - Chen, Yimin; Tu, Chao; Liu, Gang; Peng, Weidong; Zhang, Jing; Ge, Yufeng; Tan, Zhelun; Bei, Mingjian; Gao, Feng; Tian, Maoyi; Yang, Minghui; Wu, Xinbao (Frontiers in Surgery, 2024)
Background: Recent research indicates that the monocyte lymphocyte ratio (MLR), neutrophil lymphocyte ratio (NLR), platelet lymphocyte ratio (PLR), C-reactive protein (CRP), and systemic immune-inflammation index (SII) may serve as valuable predictors of early postoperative mortality in elderly individuals with hip fractures. The primary objective of the study was to examine the association between preoperative MLR, NLR, PLR, CRP, and SII levels and 3-year mortality risk in geriatric patients after hip fracture surgery. Style Definition: Normal: Font: (Asian) 宋体 Field Code Changed Field Code Changed Deleted: the risk of Deleted: over a 3-year periodPatients and methods: The study included patients aged 65 years or older who underwent hip fracture surgery between November 2018 and November 2019. Admission levels of MLR, NLR, PLR, CRP, and SII were measured. The median follow-up period was 3.1 years. Cox proportional hazards models were used to calculate the hazard ratio (HR) for mortality with adjusting for potential covariates. Time-dependent receiver operating characteristic (ROC) curves were employed to assess the predictive capability of inflammatory indicators for mortality.Results: A total of 760 patients completed the follow-up (79.4 ± 7.8 years, 71.1% female). A higher preoperative MLR was found to be significantly associated with an increased 3-year postoperative mortality risk (HR 1.811, 95% CI 1.047-3.132, P = 0.034). However, no significant correlations were observed between preoperative NLR, PLR, CRP, SII and 3-year mortality. The areas under the ROC curve (AUCs) of MLR for predicting 30-day, 120-day, 1-year, and 3-year mortality were 0.74 (95% CI 0.53-0.95), 0.70 (95% CI 0.57-0.83), 0.67 (95% CI 0.60-0.74), and 0.61 (95% CI 0.56-0.66), respectively.Preoperative MLR is a useful inflammatory marker for predicting 3-year mortality in elderly hip fracture patients, but its predictive ability diminishes over time.